Neuroprotection against 1-Methyl-4-phenylpyridinium-induced cytotoxicity by naturally occurring polydatin through activation of transcription factor MEF2D. Issue 12 (11th August 2021) - Cao, Jie; Guo, Baojian; Li, Sai; Zhang, Xaojing; Zhang, Xiaoqi; Zhang, Gaoxiao; Sun, Yewei; Wang, Yuqiang; Song, Xiubao; Zhang, Zaijun
Abstract : Polydatin is the major active ingredient of Polygonum cuspidatum Sieb. Et Zucc. A recent study indicated that polydatin could protect against substantia nigra dopaminergic degeneration in rodent models associated with Parkinson's disease. However, mechanisms that underlie the neuroprotection of polydatin have not been fully elucidated. In the current study, the neuroprotective effects and detailed mechanisms of action of polydatin were investigated in Parkinson's disease-related cellular models. Polydatin dose- and time-dependently prevented neurotoxicity caused by 1-methyl-4-phenylpyridinium ion (MPP + ) in primary cerebellar granule neurons. Moreover, we found that polydatin enhanced the activity of the transcription factor myocyte enhancer factor 2D (MEF2D) at both basal and pathological conditions using luciferase reporter gene assay. Additionally, western blot analysis revealed that polydatin could downregulate glycogen synthase kinase 3β (GSK3β), which is a negative regulator of MEF2D. Molecular docking simulations finally suggested an interaction between polydatin and a hydrophobic pocket within GSK3β. All these results suggest that polydatin prevents MPP + -induced neurotoxicity via enhancing MEF2D through the inhibition of GSK3β and that treatment with polydatin is worthy of further anti-Parkinson's disease study in future.